2020
DOI: 10.1183/13993003.02048-2019
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with isoniazid or rifampin for latent tuberculosis infection: population-based study of hepatotoxicity, completion and costs

Abstract: Clinical trials suggest less hepatotoxicity and better adherence with 4 months rifampin (4R) versus 9 months isoniazid (9H) for treating latent tuberculosis infection (LTBI). Our objectives were to compare frequencies of severe hepatic adverse events and treatment completion, and direct health system costs of LTBI regimens 4R and 9H, in the general population of the province of Quebec, Canada, using provincial health administrative data.Our retrospective cohort included all patients starting rifampin or isonia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The perception that shorter regimens would reduce medication fatigue and interference with daily life suggests that treatment completion could be improved by using shorter regimens, as has been observed in low-burden settings. 5-7 In addition, we found that caregivers were mainly concerned with having child-friendly formulations. Finally, we observed heterogeneity among participants’ regimen preferences, suggesting that adherence might be best supported by having multiple treatment options available.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The perception that shorter regimens would reduce medication fatigue and interference with daily life suggests that treatment completion could be improved by using shorter regimens, as has been observed in low-burden settings. 5-7 In addition, we found that caregivers were mainly concerned with having child-friendly formulations. Finally, we observed heterogeneity among participants’ regimen preferences, suggesting that adherence might be best supported by having multiple treatment options available.…”
Section: Discussionmentioning
confidence: 90%
“…3,4 However, shorter regimens with equal efficacy are available in high-income countries, and significantly better treatment completion has been observed under programmatic conditions. [5][6][7] Much emphasis has recently been placed on creating patient-centered models of TB care, which includes addressing individual patient needs and preferences. 8 However, there are very few published reports of patients having been asked about their preferences for preventive therapy regimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…82 Two studies from Canada showed opposite effects of provider type on treatment completion, with one showing decreased odds of treatment completion when prescribers were primary care physicians, 32 while the other found no difference in completion rates based on provider type. 140 Behavioural strategies to optimise adherence and treatment completion A prior review of reviews of IPT adherence promotion methods identified two reviews that included studies with paediatric patients, and each review included only a single study with children and adolescents. 141 The authors concluded there was little evidence supporting effectiveness of specific paediatric TPT adherence promotion strategies, although integration of TB and HIV services might improve adherence.…”
Section: Barriers and Facilitators Of Treatment Completionmentioning
confidence: 99%
“…Some of medicines, such as tetracycline, doxycycline, minocycline, and erythromycin, may be able to further suppress the inflammatory response to relieve pain for patients [ 5 ]. However, long-term or overuse of antibiotics may generate microbial drug resistance and/or induce detrimental side effects, such as pigmental change, atrophy, skin irritation, hepatotoxicity, and/or birth defects [ 6 , 7 , 8 , 9 , 10 ], that highly hinder the utilization of antibiotics in the clinic.…”
Section: Introductionmentioning
confidence: 99%